Do Behavioral Interventions Enhance the Effects of Cash on Early Childhood Development and Its Determinants? Evidence from a Cluster-Randomized Trial in Madagascar - Datta, Saugato; Martin, Joshua; MacLeod, Catherine; Rawlings, Laura B.; Vermehren, Andrea (World Bank, Washington, DC, 2021)
This paper evaluates the effects of interventions based on behavioral science on measures of early childhood socio-cognitive development (and related household-level outcomes) for children from households receiving cash transfers in Madagascar, using a multi-arm cluster-randomized trial. Three behavioral interventions (a Mother Leaders group and associated activities, by itself or augmented with a self-affirmation or a plan-making nudge) are layered onto a child-focused cash transfer program targeting children from birth to age six years. Approximately 18 months into the implementation of these interventions and 20 months since baseline, the study finds evidence that households in the behaviorally enhanced arms undertake more desirable parenting behaviors, interact more with their children, prepare more (and more diverse) meals at home, and report lower food insecurity than households that received only cash. Children from households in several of the behaviorally enhanced arms also perform better than children from households in the cash-only arm on several measures of socio-cognitive development, including language learning and social skills.